Odpowiedzi

  • Użytkownik Zadane
2010-01-20T23:22:23+01:00
4(2x+3)-2(4y-1)=30
5x+1 /3 - y-3 /4 = 3

8x+12-8y+2=30
20x+4 /12 - 3y-9 /12 = 3

8x-8y=16
20x+4-3y+9=36

x-y=2
20x-3y=23

-3x+3y=-6
20x-3y=23

17x= 17
x=1
1-y=2
y=-1

x=1
y=-1
Najlepsza Odpowiedź!
2010-01-20T23:23:49+01:00
{4(2x+3)-2(4y-1)=30
{(5x+1):3-(y-3):4=3 /*12

8x+12-8y+2=30
4(5x+1)-3(y-3)=36

8x-8y=16 /:8
20x+4-3y+9=36

x-y=2
20x-3y=23

x=2+y
20(2+y)-3y=23

x=2+y
40+20y-3y=23

x=2+y
17y=-17

x=2+y
y=-1

x=2-1
y=-1

x=1
y=-1
2010-01-20T23:24:01+01:00
{4(2x+3)-2(4y-1)=30
{(5x+1):3-(y-3):4=3

8x+12-8y+2=30
4(5x+1)/12-3(y-3)/12=3

8x=16+8y
(20x+4)/12-(3y-9)/12=3

x=2+y
(20x+4-3y+9)/12=3

20(2+y)+4-3y+9=36
40+20y+4-3y+9=36
17y=-17
y=-1

x=2+(-1)
x=1

x=1
y=-1